Orexin/hypocretin system dysfunction in patients with Takotsubo syndrome: A novel pathophysiological explanation - Knez, Rajna; Niksic, Milan; Omerovic, Elmir (Frontiers in Cardiovascular Medicine, 2022)
Takotsubo syndrome (TTS) is an acute heart failure syndrome. Emotional or physical stressors are believed to precipitate TTS, while the pathophysiological mechanism is not yet completely understood. During the coronavirus disease (COVID-19) pandemic, an increased incidence of TTS has been reported in some countries; however, the precise pathophysiological mechanism for developing TTS with acute COVID-19 infection is unknown. Nevertheless, observing the symptoms of COVID-19 might lead to new perspectives in understanding TTS pathophysiology, as some of the symptoms of the COVID-19 infection could be assessed in the context of an orexin/hypocretin-system dysfunction. Orexin/hypocretin is a cardiorespiratory neuromodulator that acts on two orexin receptors widely distributed in the brain and peripheral tissues. In COVID-19 patients, autoantibodies against one of these orexin receptors have been reported. Orexin-system dysfunction affects a variety of systems in an organism. Here, we review the influence of orexin-system dysfunction on the cardiovascular system to propose its connection with TTS. We propose that orexin-system dysfunction is a potential novel explanation for the pathophysiology of TTS due to direct or indirect dynamics of orexin signaling, which could influence cardiac contractility. This is in line with the conceptualization of TTS as a cardiovascular syndrome rather than merely a cardiac abnormality or cardiomyopathy. To the best of our knowledge, this is the first publication to present a plausible connection between TTS and orexin-system dysfunction. We hope that this novel hypothesis will inspire comprehensive studies regarding orexin's role in TTS pathophysiology. Furthermore, confirmation of this plausible pathophysiological mechanism could contribute to the development of orexin-based therapeutics in the treatment and prevention of TTS.